MATHEMATICAL AND STATISTICAL ANALYSIS AND FORECASTING OF EMPLOYMENT INDICATORS IN THE FERGANA REGION - Obidjonova Diyora Omonjon kizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the dynamics of employment indicators in the Fergana Region during 2017–2024 using mathematical and statistical methods. During the study, trends in employment levels were examined based on statistical data, and regression analysis and forecasting methods were applied. The main factors affecting employment, including demographic growth, economic development, labor market demand and supply, and the development of entrepreneurial activities, were evaluated. In addition, forecast values of employment indicators up to 2030 were calculated using mathematical models. The results of the study are of significant practical importance for increasing employment levels, developing the labor market, and formulating an effective employment policy in the Fergana Region.